IMPLEMENTASI KEBIJAKAN PELAYANAN PUBLIK PADA MAL PELAYANAN PUBLIK KOTA PAYAKUMBUH - Yossa Fitria; Roni Ekha Putera (Halu Oleo University, 2024)
The policy for implementing the Public Service Mall in Payakumbuh City is a renewal as well as a strategic step in an effort to improve public services that are fast, easy, affordable, safe, and comfortable. The aim of the research is to identify the methods, techniques, or strategies that have been carried out by the Payakumbuh City Government in implementing public service policies at the Payakumbuh City Public Service Center. This research uses the policy implementation model proposed by George Edwards III. Policy implementation is examined from four perspectives, namely: communication, resources, disposition, and bureaucratic structure. The research uses qualitative methods, with data collection techniques through interviews, observation, and documentation. In general, the research results illustrate that the implementation of the Public Service Mall in Payakumbuh City has been running well in accordance with applicable regulations, so it received an award from the Indonesian Ombudsman with the highest score in West Sumatra Province as the city organizes compliance with public service delivery in 2023.